Factors Influencing The Total Sales of Fruits and Vegetables on Digital Platforms - Diah Khairani; Yusman Syaukat; Sugeng Budiharsono (Jurnal Manajemen dan Agribisnis, 2022)
The development of digital technology and a pandemic have increased online transactions on digital platforms. The most widely used digital platforms for online transactions in Indonesia are Shopee, Tokopedia, and Bukalapak. Digital platforms will become essential actors in the agribusiness system in the future. Fresh agricultural products marketed on digital platforms are included in the fruit and vegetable category. This research aims to analyze the factors that influence the total sales of fruits and vegetables on the digital platforms. The method used in this research is panel data regression. The results show that the effect is positive and negative based on types of products. The number of reviews through digital platforms influences significantly on total fruit and vegetable sales. However, the price does not influence significantly on total sales. Meanwhile, other factors include rating, store type, and promotion provide results of varying significance by commodity. Because review is the most important factor that affect total sales in digital platforms, seller needs to focus on how to control reviews in each digital platform. The understanding can help the seller to increase their total sales. Keywords: digital farmer, e-commerce, marketing, marketplace, robust least squares